2013
DOI: 10.1016/j.ejon.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms in the cancer patient – Of importance for their caregivers' quality of life and mental health?

Abstract: Subtitle: Cancer patients' symptoms affecting caregivers' quality of life and mental health Results:The main result showed that the symptom burden was close to equal when we compared the cancer patients in the palliative and the curative phase respectively. The whole sample of patients seemed extremely tired because they score high on items capturing fatigue or weakness. They also had problems with pain and constipation. For patients having trouble sleeping, the caregivers' reported higher level of depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 40 publications
3
29
1
5
Order By: Relevance
“…One possible explanation for this is that the high education populations are more likely to have a high expectation of healthy life and family, while the contradiction between cancer reality and their expectation may make them in emotional distress (Demirbag, 2012). Another finding was that patients' symptom has a significant adverse effect on caregivers mental QOL that was consistent with studies of symptom related to cancer in America and Norway (Palos et al, 2011;Valeberg et al, 2013). This finding indicated the importance of symptom management.…”
Section: Discussionsupporting
confidence: 77%
“…One possible explanation for this is that the high education populations are more likely to have a high expectation of healthy life and family, while the contradiction between cancer reality and their expectation may make them in emotional distress (Demirbag, 2012). Another finding was that patients' symptom has a significant adverse effect on caregivers mental QOL that was consistent with studies of symptom related to cancer in America and Norway (Palos et al, 2011;Valeberg et al, 2013). This finding indicated the importance of symptom management.…”
Section: Discussionsupporting
confidence: 77%
“…The authors suggest that the elevated levels of anxiety may be related to concerns about the future and fear of loss and loneliness, issues of special relevance to impending death. However, the quality of life and anxiety do not difer signiicantly between caregivers in the palliative and curative stages of the disease, suggesting that both phases are equally stressful and challenging [58] and always include a concern about the future. However, in another study [59], clinically signiicant levels of depressive symptomatology were found, which did not change markedly over time of the disease.…”
Section: Cancermentioning
confidence: 99%
“…Douglas ve Dally da kanser hastalarının fiziksel yaşam kalitesi ve bakım vericilerin depresyonu arasında negatif ve orta düzeyde ilişki bulmuşlardır. Hastanın spirituel iyilik halinin, hastanın yaşam kalitesi ve bakım vericinin depresyonu arasında önemli derecede rol oynadığını, bakım vericinin depresyonunu azaltmak için hastanın spirituel sorunlarına odaklanmak gerektiğini vurgulamışlardır 21,23,32 . Frıdrıksdottır ve arkadaşları bakım vericilerin %41'inin depresif belirtiler, %20'sinin de anksiyete deneyimlediklerini, anksiyetenin de kadın bakım vericilerde daha yüksek düzeyde olduğunu saptamışlardır.…”
Section: Kanserli Hastaya Bakım Veren Bakım Vericilerin Duygusal Yaşaunclassified
“…Bakım vericilerin sosyalliklerinin azaldığı ve günlük planlarının olumsuz etkilendiği çalışmalarda bildirilmiştir 24,23 .…”
Section: Sonuçunclassified